Embedding biodiversity research into climate adaptation policy and practice. (16th July 2021) - Graham, Victoria; Auld, Tony; Beaumont, Linda; Bell, Linda; Dunford, Suzanne; Gallagher, Rachael; Hancock, Nola; Leishman, Michelle R.; Mitchell, Polly; Staas, Leigh; Hughes, Lesley
Abstract: Addressing climate change risks requires collaboration and engagement across all sectors of society. In particular, effective partnerships are needed between research scientists producing new knowledge, policy‐makers and practitioners who apply conservation actions on the ground. We describe the implementation of a model for increasing the application and useability of biodiversity research in climate adaptation policy and practice. The focus of the program was to increase the ability of a state government agency and natural resource practitioners in Australia to manage and protect biodiversity in a changing climate. The model comprised a five‐stage process for enhancing impact (i) initiation of research projects that addressed priority conservation policy and management issues; (ii) co‐design of the research using a collaborative approach involving multiple stakeholders; (iii) implementation of the research and design of decision tools and web‐based resources; (iv) collaborative dissemination of the tools and resources via government and community working groups; and (v) evaluation of research impact. We report on the model development and implementation, and critically reflect on the model's impact. We share the lessons learnt from the challenges of operating within a stakeholder group with diverse objectives and criteria for success, and provide a template for creating an environmental research program with real world impact. Abstract : Here we present an engagement approach of a partnership that embedded biodiversity research into climate adaptation policy and on‐ground natural resource management. We report on the collaborative approach developed for the program and provide examples of successes, challenges and lessons learnt. We draw from the different perspectives of policy‐makers, research scientists and conservation practitioners to evaluate the initial progress towards achieving intended impacts and present a roadmap for creating partnerships that have lasting impact.